PENGARUH MEDIA DIORAMA TERHADAP KETERAMPILAN BERBICARA - Ma’ Rifah, Shofia; Subekti, Tabah (Universitas Muhammadiyah Magelang, 2013)
This study aims to determine the effect of media on students’ speaking skills diorama Class IV Elementary School 1 Maduretno Kalikajar District of Wonosobo. The method used is experiment with this type of pre-experimental designand experimental models one group pretest posttest design of data collection instruments while this study of an oral test sheet. Samples were fourth grade students of State Elementary School 1 Maduretno, District Kalikajar, Wonosoboregency school with the number of 20 subjects, data analysis using statistical techniques with Wilcoxon Signed Test Rank. The results showed that the media diorama effect in the skills of speaking at State Primary School 1 Maduretno, District Kalikajar, Wonosobo regency. It is evident the increase in the average value of the initial measurement (pretest) 51.65 into 68.40 on the average value of measurement end (posttest) by a margin of 16.75 and Asym sign = 0,000 <α = 0.05 with value Z -3926. This means that the hypothesis which states that: “Media diorama effect on the speaking skills”, accepted and proven his righteousness. The conclusions of this study is the speaking skills of students has increased after being treated in the form of media diorama. Master class IV diorama can use the media as an alternative medium of learning in learning Indonesian spoke aspects to improve students’ speaking skills. Based on these results, the media diorama effect on conversational skills.